Equivalência de estímulos e o ensino de relações numéricas para crianças com transtorno do espectro do autismo - Picharillo, Alessandra Daniele Messali (2020)
The aim of the present study was to evaluate the effects of teaching between spoken number, Arabic number and quantity, using a computerized matching-to-sample procedure, through stimuli equivalence paradigm and to evaluate the generalization making use of manipulable materials. Participants were five students with students with Autism Spectrum Disorder (ASD), from 4 to 10 years old, with receptive language and unknown to the knowledge to be taught. A pre- and post-test design was used to evaluate the generalization for manipulable materials, as well as a multiple probes across groups of stimuli design. In the present study, the independent variable was the teaching of the relations between the stimuli (dictated numeral, Arabic numeral and quantity) through the matching to sample procedure, using a computer, and the dependent variable was the participants’ performance in training and equivalence relations (both in computerized and manipulable conditions). The procedure included the teaching of the relations between dictated numerals and Arabic numerals (AB) and between dictated numerals and quantity represented by circles (AC), followed by transitivity tests (Arabic numerals and quantity relation – BC; and quantity and Arabic numerals relation – CB) for each of the three stimuli groups. Before and after teaching and testing each stimuli group, the AB, AC, BC and CB relations were evaluated using stimuli from the three groups. Generalization tests with manipulable material (AD and BD relations) were conducted in the beginning and in the end of the procedure. The results showed that the participants learned the taught relations between dictated numeral and printed numeral (AB) and dictated numeral and quantity (AC), and they also showed the emergence of the relations between Arabic numeral and quantity (BC) and between quantity and Arabic numeral (CB), with the need for different numbers of intra- and inter-participant sessions until mastery. The results indicate that the learning of each group of stimuli occurred after the insertion of the independent variable. Regarding the generalization test, four participants (Miguel, Laura, Tiago and Ana) presented a percentage above 75% of correct responses in the printed number-quantity (BD) and dictation number-quantity (BD) relations, and one participant (Lucas) presented a percentage below 30% of correct responses. The data showed that the equivalence class formation paradigm can be a resource to be used for teaching the relations between dictated number, Arabic numeral and quantity with participants with ASD.